Influence of parental involvement on academic achievement - Ngu, Leh Seng; Hanafi, Zahyah; Taslikhan, Muhajir (2016)
Parental involvements in children’s education are prioritized by the Ministry of Education. Parental involvement in education means that the relationship of parents and children to achieve academic success. This study aims to identify the level of parental involvement and the influence of parental involvement on children's academic achievement. This study involved 406 Form Five students in nine schools in Limbang, Sarawak, Malaysia.Inventory of Parental Influence, The Paternal Involvement and Maternal Involvement Scale are used in this study.Descriptive statistical methods to test the parental involvement while the SEM-PLS is use to examine the influence of parental involvement in academic achievement.The findings show that the level of parental involvement are high.There is a significant influence of parental involvement on children's academic achievement.Parents are encouraged to engage in continuous involvement in their children’s education.